PENERAPAN MODEL PEMBELAJARAN PROBLEM-BASED LEARNING UNTUK MENINGKATKAN PARTISIPASI DAN PRESTASI BELAJAR SISWA - Yasminah Yasminah; Bambang Sahono (UNIB Press, 2020)
This study aims to describe the application of problem-based learning (PBL) learning models to increase participation and business learning achievement of X grade students of Online Business and Marketing (BDP) of SMK Negeri 2 Lahat. The research model used is Classroom Action Research (CAR) and quasi experimental. The subjects of the research were the first semester students of X BDP class in the academic year 2019/2020 of SMK Negeri 2 Lahat. For the quasi-experimental sample is X OTKP 1 and X OTKP 2 class. The number of students for the PTK class is 30 students, for the Experiment class there are 30, and for the control class there are 30 students. Data collection methods in this study used observation sheets of PBL model learning implementation, participant observation sheets and learning outcomes tests. Data analysis uses mean, and t-test consisting of inter-cycle difference tests and two unrelated sample different tests. From the results of the study indicate that the application of PBL learning models can increase participation, and learning achievement in business communication subjects in SMK Negeri 2 Lahat.